Mitigation of atmospheric phase delay in InSAR time series using ERA-interim model, GPS and MODIS data: application to the permafrost deformation in Hurd Peninsula, Antarctica - Reis, A. R. (2018)
In this study we compare the results obtained using three different atmospheric datasets for the mitigation of atmospheric effects in TerraSAR-X imagery. The used datasets are: ERA-interim re-analysis model, MODIS sensor precipitation water vapour data and GPS derived precipitable water vapour (PWV). The PWV maps were converted to atmospheric path delay and projected into the SAR interferograms geometry. Subsequently the PWV contribution was removed from the interferograms. The Persistent Scatterers technique was applied to the atmospherically corrected interferograms and the obtained displacement rate compared with GPS surface displacement. It was observed that the mitigation of atmospheric effects influences the estimated displacement rate.